Nest biology and demography of the fungus-growing ant cyphomyrmex lectus forel (Myrmicinae: Attini) at a disturbed area located in Rio Claro-SP, Brazil - Ramos-Lacau, L. S.; Silva, P. S.D.; Delabie, J. H.C.; Lacau, S.; Bueno, O. C. [UNESP] (Universidade Estadual de Feira de Santana, 2015)
Cyphomyrmex ants are a basal group of small fungus-growers (Myrmicinae:Attini), which differ profoundly from their most studied relatives Atta and Acromyrmex. Our objective was to investigate the nest biology and demography of the fungus-growing ant Cyphomyrmex lectus in a transitional area (savanna-forest) disturbed by an annual fire regime, in Southeast Brazil. The colonies of C. lectus were located close to each other (mean distance between nests, 3.38 ± 2.75 m). Its external nest structure consisted of a single circular nest-entrance hole but without a conspicuous nest mound. Nests were relatively simple consisting of a single well-formed chamber and a single gallery connecting to the nest entrance. No relationships were found between ant number per colony and gallery length, as well as chamber volume. Nonetheless, we detected an effect of the ant number per colony on chamber depth. In this sense, a deeper chamber could warrant a better protection against fire, natural enemies and offer favorable micro-conditions to yeast culture. The colonies of C. lectus are small (a mean of 70 ± 49.4 individuals/colony). Alates, larvae and pupae were found only in one out of eight colonies. A single dealate queen per colony was observed strongly suggesting that this species is monogynous. Further studies could evaluate whether (1) nests density differ before and after fire periods, (2) fire occurrence affects the survival and establishment rate of new colonies, as well as (3) the nest microclimatic conditions necessary to yeast culture.
Keywords: Colony; Establishment; Fire